Experimental Investigation of the Cubic, Cylindrical, and Pile-shaped Obstacles on the Motion and Control of the Body of Saline Density Current - Mohammad Reza Mansoujian; Mehdi Ghomeshi; Houshang Hasounizadeh; Seyed Abbas Hosseini (مهندسی منابع آب, 2023)
Abstract Introduction: The use of obstacles in dam reservoirs is considered an effective method for directing sedimentation toward the middle of the reservoir (instead of sedimentation next to the dam wall where the facilities are located). In the present study, to control the saline density current, the effect of cylindrical, cubic, and pile-shaped obstacles on the characteristics and motion of the body of the density is experimentally investigated. Methods: In this regard, 323 cylindrical obstacles with a diameter of 1 cm and a height of 30 cm, were placed on the bed of a Plexiglas in a channel with a length of 12.5 m, a width of 30 cm, and a height of 40 cm in a zigzag form along with the same number of cubic obstacles with dimensions of 1.1 cm and a height of 30 cm in the next step. The experiments were performed with three flow rates (0.27, 0.55, and 0.83 liters per second), three slopes (0.2, 0.5, and 1%), and constant concentration (15 g/l). Findings: The results showed that the use of obstacles reduces the height of the body of density current along the channel. The height of the body in cubic obstacles is more than cylindrical obstacles. The use of obstacles affects the velocity profiles and reduces the velocity of the body of the density current. The flow rate of the body of density current in a bed without obstacles has an increasing trend while it has a decreasing trend in the bed with obstacles. Therefore, the reduction of flow rate in cubic obstacles was 1.5 to 2 times compared to the cylindrical obstacles. As a result, flow rate control in cubic obstacles was greater. Also, by moving along the channel, the reduction of the concentration of body of the density current in cubic and cylindrical obstacles was 49% and 41%, respectively, compared to the bed without obstacle